Assessing strength of evidence for regulatory decision making in licensing: What proof do we need for observational studies of effectiveness?. Issue 10 (16th April 2020) - Slattery, Jim; Kurz, Xavier
Abstract: Before a medicine can be recommended for a marketing authorization research must be provided to regulators that convincingly supports the benefit‐risk of the product in the claimed indication. The established criteria for such research are usually expressed in terms of evidence from randomized controlled trials (RCT). If studies in real‐world data (RWD) are to be accepted as all or part of the package of evidence, it is necessary to understand the relationship between information from studies of RWD and that from RCTs. The aim of this review is to consider how the strength of such evidence can be quantified in a manner that relates to the decision‐making process, what research is currently available to further this understanding and what additional information will be required.